Different Aspects of Internationalisation and Their Ramifications – Opportunities and Risks - Jana-Larissa Grzeszkowiak (European Institute for Knowledge & Value Management (EIKV), 2023)
[Preface:] The world we are living in is in continuous transition. Although the history of humanity dates back around 300.000 years and humanity has always experienced transition, the processes of transition have intensified and densified exponentially like over that period of time. While only few transition processes occurred and took long duration in the ancient times, they occur more frequently and happen quicker nowadays. One of the most profound transitions influencing all our lives is the increasing internationalisation. Due to increased mobility and new information and communication technologies the world in general, but likewise nations and their citizens, get more and more interconnected. Internationalisation influences all aspects of our lives and comes along with risks but at the same time with opportunities. Whereas cultural exchange may erode cultural identity through over-adaption of foreign peculiarities, it offers opportunities for elevated self-development and self-expression. (...)
Keywords: 300